Development Of Games And Teaching Media For Catholic Religion Primary School Teachers - Seva, Kristining; Simanjuntak, Mardohar Batu Bornok; Sirait, Asnita (LPPM Universitas PGRI Sumatera Barat, 2025)
This devotion takes priority method studies documentation through observation, interview, study libraries, and also training that places application draft method teaching interactive in education Budi character For increase teaching ability of Catholic religious teachers at elementary school level throughout West Java, with scheme Work The same partner with BIMAS Catholic, Ministry of Religion of West Java Province. Besides that, implementation method teaching interactive for teachers it is also useful For support performance teaching. Hence, reinforcement education religion is also close connection with strengthening character based on Catholicism would be more interesting If be delivered in method interactive teaching based game. Training about method teaching, creating teaching media (online and offline), becoming content training for these teachers the in this devotion.